The Changing Landscape in Pediatric Hospitals: A Multicenter Study of How Pediatric Chronic Critical Illness Impacts NICU Throughput - Boss, Renee D.; Henderson, Carrie M.; Weiss, Elliott M.; Falck, Alison; Madrigal, Vanessa; Shapiro, Miriam C.; Williams, Erin P.; Donohue, Pamela K.; on behalf of the Pediatric Chronic Critical Illness Collaborative (American Journal of Perinatology, 2020)
Objective Pediatric inpatient bed availability is increasingly constrained by the prolonged hospitalizations of children with medical complexity. The sickest of these patients are chronic critically ill and often have protracted intensive care unit (ICU) stays. Numbers and characteristics of infants with chronic critical illness are unclear, which undermines resource planning in ICU's and general pediatric wards. The goal of this study was to describe infants with chronic critical illness at six academic institutions in the United States.Study Design Infants admitted to six academic medical centers were screened for chronic, critical illness based on a combination of prolonged and repeated hospitalizations, use of medical technology, and chronic multiorgan involvement. Data regarding patient and hospitalization characteristics were collected.Results Just over one-third (34.8%) of pediatric inpatients across the six centers who met eligibility criteria for chronic critical illness were <12 months of age. Almost all these infants received medical technology (97.8%) and had multiorgan involvement (94.8%). Eighty-six percent (115/134) had spent time in an ICU during the current hospitalization; 31% were currently in a neonatal ICU, 34% in a pediatric ICU, and 17% in a cardiac ICU. Among infants who had been previously discharged home (n = 55), most had been discharged with medical technology (78.2%) and nearly all were still using that technology during the current readmission. Additional technologies were commonly added during the current hospitalization.Conclusion Advanced strategies are needed to plan for hospital resource allocation for infants with chronic critical illness. These infants' prolonged hospitalizations begin in the neonatal ICU but often transition to other ICUs and general inpatient wards. They are commonly discharged with medical technology which is rarely weaned but often escalated during subsequent hospitalizations. Identification and tracking of these infants, beginning in the neonatal ICU, will help hospitals anticipate and strategize for inpatient bed management.Key Points
Keywords: chronic illness; pediatrics; intensive care